STUDI KOMPARATIF KOMPETENSI PEDAGOGIK GURU PKn BERDASARKAN LATAR BELAKANG PENDIDIKAN - Dania Evirianti; Irawan Suntoro; Yunisca Nurmalisa (FKIP Unila, 2014)
The purpose of this study is to describe teachers’ pedagogic competence. The research approach used is an evaluative study. The next data is analyzed by comparing teachers’s data and background of civic education and noncivic education. The results on 32 teacher on SMP Swasta Kecamatan Kedaton indicate that: (1)Planning of learning by teachers has been implemented in good category, including the clarity of the formulation of learning objectives, materials selection, organizing materials, selection of sources/media learning, scenario clarity, detail of the scenario, the suitability and completeness of the technique by learning and instrument learning. (2)Implementation of learning by teachers has been implemented in good category, which includes the use of method, media and means of learning. School teachers have done to start learning with the introduction, opening and cover the core activities. (3)Evalution of learning by teachers has been implemented in good category, which includes the program and implementation of remedial, carry out assessments and implement affective personality assessment of motoric skills.Tujuan penelitian ini adalah mendeskripsikan kompetensi pedagogik guru. Data selanjutnya di analisis dengan membandingkan data guru berlatar belakang pendidikan Pkn dan Pendidikan nonPKn. Hasil penelitian yang dilakuakan terhadap 32 guru SMP Swasta Kecamatan Kedaton menunjukan : (1) Perencanaan pembelajaran oleh guru masuk dalam kategori baik meliputi kejelasan perumusan tujuan pembelajaran, pemilihan bahan ajar, pengorganisasian bahan ajar, pemilihan sumber/media pembelajaran, kejelasan scenario, kerincian scenario, kesesuaian teknik dan kelengkapan instrument pembelajaran. (2) Pelaksanaan pembelajaran oleh guru masuk dalam kategori baik, meliputi penggunaan metode, media dan sarana pembelajaran. Guru sudah melakukan memulai pembelajaran dengan pendahuluan, pembukaan, kegiatan inti dan penutup. (3)Evaluasi pembelajaran oleh guru masuk dalam kategori baik, mencakup program dan pelaksanaan remedial, melaksanakan penilaian afektif kepribadian dan melaksanakan penilaian kemampuan motorik.Kata kunci: kompetensi pedagogik, latar belakang pendidikan, PKn